Matrine derivate MASM protects murine MC3T3-E1 osteoblastic cells against dexamethasone-induced apoptosis via the regulation of USP14/p53. Issue 1 (4th December 2019) - Zhou, Panyu; Xia, Demeng; Wang, Yang; Lv, Hongdi; Wang, Ziqin; Xing, Malcolm; Zhao, Qingjie; Xu, Shuogui
Abstract: Matrine derivative MASM (M19) is a quinolizine alkaloid with diverse pharmacological effects including preventing postmenopausal osteoporosis. In the current study, we observed that pretreatment with M19 inhibited cell apoptosis of murine osteoblastic MC3T3-E1 and primary osteoblasts induced by 1 μM dexamethasone in a dose-dependent manner. Our study also showed that pretreatment with M19 significantly prevented the upregulation of p53 that is caused by dexamethasone but had no effect on the p53 mRNA expression levels. Further immunoprecipitation (IP) experiments showed that M19 treatment increases the ubiquitination of p53 in dexamethasone-treated MC3T3-E1 cells. The expression of USP14, a deubiquitinating enzyme, increased with dexamethasone and decreased with M19 pretreatment. Co-IP experiments demonstrated the interaction between USP14 and p53, and the induced effect of a USP14 inhibitor (IU1) on p53 ubiquitination, which indicated that USP14 is a potential deubiquitinase for p53. Furthermore, pretreatment with IU1 or a p53 inhibitor (PFT-α) partially blocked dexamethasone-induced apoptosis of MC3T3-E1 cells. The overexpression of USP14 or p53 reversed the antiapoptotic effect of M19 in dexamethasone-treated MC3T3-E1 cells. In addition, PFT-α treatment remarkably blocked the effects of USP14 overexpression. In summary, our findings suggest that M19 exerts protective effects on dexamethasone-treated MC3T3-E1 cells by regulating USP14/p53.